2020
DOI: 10.5937/socpreg54-27595
|View full text |Cite
|
Sign up to set email alerts
|

Family practices during the pandemic and the state of emergency: The female perspective

Abstract: Pojačani rizici inspirativan su kontekst za analizu porodičnih praksi, jer mogu da utiču na njihove promene, a time i na promene porodičnog funkcionisanja i odnosa. Cilj rada je da se utvrde obeležja osnovnih porodičnih praksi (reprodukcija svakodnevice, partnerstvo, roditeljstvo) u uslovima pandemije i vanrednog stanja u srpskom društvu. Pretpostavka je da su navedeni uslovi doveli do njihovih promena. Podaci za analizu prikupljeni su na uzorku od 265 ispitanica primenom kombinovanog istraživačkog plana. Rezu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 7 publications
2
24
0
1
Order By: Relevance
“…Similar was concluded in the research ofČikić and Bilinović-Rajačić (2020): the authors stated that practice of housework "involving woman as the main actor remained unchanged in ¾ of families in which it was present before, in spite of the fact that women reported performing additional activities in the novel situation or lacking the help they had before the state of emergency was declared". In the families with established practice of egalitarian participation of partners in housework, such arrangements were spontaneous or planned(Čikić and Bilinović-Rajačić, 2020). 13 Data source: https://www.worldometers.info/coronavirus/ (accessed 17/10/2020) 14 Data source: https://lab24.ilsole24ore.com/coronavirus/ (accessed 17/10/2020)…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Similar was concluded in the research ofČikić and Bilinović-Rajačić (2020): the authors stated that practice of housework "involving woman as the main actor remained unchanged in ¾ of families in which it was present before, in spite of the fact that women reported performing additional activities in the novel situation or lacking the help they had before the state of emergency was declared". In the families with established practice of egalitarian participation of partners in housework, such arrangements were spontaneous or planned(Čikić and Bilinović-Rajačić, 2020). 13 Data source: https://www.worldometers.info/coronavirus/ (accessed 17/10/2020) 14 Data source: https://lab24.ilsole24ore.com/coronavirus/ (accessed 17/10/2020)…”
supporting
confidence: 69%
“…Changes in food purchase practices could also be linked to characteristics of eating practices. Namely, health risks, closed restaurants and bars, and frequent lockdowns during the pandemic and the state of emergency, have forced eating practices to be "back home" again (Čikić and Bilinović Rajačić, 2020). The research results on family practices have shown that cooking and eating at home are more frequent during the pandemic than usual, and re-domestication 19 of cooking and eating practices have caused the increase in quantities of purchased food.…”
Section: Food Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Посебно у кризним временима, каква је ситуација сада у току пандемије COVID-19, породица је на себе поново преузела неке од функција институционалне социјализације (в. Pajević, Fehratović, 2021), док су друга истраживања показала како је дошло до промена у породичним праксама које су измењене у правцу већег егалитаризма унутар породице, већег учешћа оца-мужа (ванбрачног мушког партнера) у обављању послова у домаћинству, васпитавању деце (Čikić, Bilinović Rajačić, 2020). Оживљавање ширих сродничких веза и интензивирање рођачких односа примећено је и раније, посебно у друштвима која су у кризи.…”
Section: тзв "истополне заједнице" нису нити могу да буду исто што и породица и бракunclassified
“…Finally, through creating the family, blood relations are developed (as well as those imitating them based on the adoptive relations), including other types of relationships, which connect people on more solid foundations, creating and expanding groups of relatives. It is in periods of crisis, such as the current situation caused by the COVID-19 pandemic, that the family has once again assumed some of the functions of institutional socialization (see Pejević, Fehratović, 2021), while other studies have shown the changes occurring in family practices that have already been modified towards greater egalitarianism within the family, greater participation of the father/husband (common-law male partner) in doing housework and in children upbringing (Čikić, Bilinović Rajačić, 2020). Reviving kinship ties and intensifying relations with relatives has been observed earlier too, particularly in crisis-stricken societies.…”
mentioning
confidence: 99%